Efficacy and safety of mycophenolate mofetil in patients with active moderate‐to‐severe Graves' orbitopathy. (7th September 2016) - Ye, Xiaozhen; Bo, Xiaoyong; Hu, Xiaohao; Cui, Huanhuan; Lu, Bin; Shao, Jiaqing; Wang, Jian
Summary: Context: Graves' orbitopathy (GO) is a potentially sight‐threatening disease for which currently available medical therapy is not reliably successful. Mycophenolate mofetil (MMF) is a selective immunosuppressant used widely in many autoimmune diseases. Preliminary studies have shown that MMF is effective in the treatment of active GO. Objective: To evaluate the efficacy and safety of MMF in patients with active moderate‐to‐severe GO. Patients: One hundred and 74 patients with active moderate‐to‐severe GO were randomized to receive either MMF or glucocorticoids (GC). Main Outcome Measures: The primary outcome was overall response at the 12th and 24th weeks; the outcome assessments included clinical activity score (CAS), soft tissue involvement, pain, visual acuity, proptosis, diplopia and reduction in eye movements. The secondary outcome was changes in those individual parameters. Adverse effects were recorded at each visit. Results: A greater overall response rate was found in the MMF group compared with the GC group at the 24th week (91·3% vs 67·9%, P = 0·000). MMF therapy showed a better CAS response than GC (92·5% vs 70·5% improved, P < 0·05). Patients treated with MMF showed a significantly improved rate of diplopia and proptosis than patients treated with GC at the 24th week (90·4% and 68·8% improved, respectively). Disease reactivation was not observed in the patients treated with MMF but was observed in five patients after GC therapy. Adverse events occurred in 4 of 80 patients treated with MMF (5%), all of which were mild to moderate. A severe adverse event was only observed in one patient treated with GC but not at all in patients treated with MMF. Conclusion: Compared with GC treatment, MMF therapy is more effective and safer for patients with active moderate‐to‐severe GO.